Proceedings of Conference on Electrical Insulation and Dielectric Phenomena - CEIDP '96
DOI: 10.1109/ceidp.1996.564717
|View full text |Cite
|
Sign up to set email alerts
|

Performance of polymer concrete insulators in Latin America

Abstract: Polymer concrete is a relatively low-cost composite material system that has been developed to be a technically viable alternative to porcelain for most high voltage electrical insulation applications (both outdoor and indoor). Following the early development of the material at WestinghouseR&D under the sponsorship of the Electric Power Research Institute, numerous additional R&D projects/studies have been carried out both in the U.S. and abroad. The material is now utilized by many utilities and accepted by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The dielectric strengths of the PCCs from this study showed values between 6.1 and 16.5 kV/mm, which are within the ranges obtained for common insulating materials such as glass (5-10 kV/mm) and electro-ceramics (8-15 kV/mm) [33]. Other studies also indicated that PCCs incorporating acrylic and vinyl ester have dielectric strengths between 6 and 9 kV/mm [34,35]. Consequently, the PCC mixes developed in this study provided adequate dielectric strengths to be applied in most high-voltage insulating systems.…”
Section: Dielectric Strengthsupporting
confidence: 84%
See 1 more Smart Citation
“…The dielectric strengths of the PCCs from this study showed values between 6.1 and 16.5 kV/mm, which are within the ranges obtained for common insulating materials such as glass (5-10 kV/mm) and electro-ceramics (8-15 kV/mm) [33]. Other studies also indicated that PCCs incorporating acrylic and vinyl ester have dielectric strengths between 6 and 9 kV/mm [34,35]. Consequently, the PCC mixes developed in this study provided adequate dielectric strengths to be applied in most high-voltage insulating systems.…”
Section: Dielectric Strengthsupporting
confidence: 84%
“…Conversly, the dielectric loss factor of the PCC showed much higher values than other types of widely used insulating materials such as cross-linked polyethylene (from 10-3 to 10-4) and SF6 gas (less than 10-7) under a frequency of 50 Hz [40][41][42]. Based on these results, the low cost and high durability of the PCC materials also provide the potential for application of such materials in cable protection covers and high-voltage insulators [34].…”
Section: Dielectric Lossmentioning
confidence: 91%